DESIGN OF EXPERIMENT-BASED CANDESARTAN CILEXETIL NANOCRYSTALS LOADED SOLID DISPERSION FOR ORAL DRUG DELIVERY SYSTEM: OPTIMIZATION, IN VITRO/IN VIVO EVALUATION - SONALI VIJAYKUMAR MAGDUM; PRAMODKUMAR JAYKUMAR SHIROTE (Asian Journal of Pharmaceutical and Clinical Research, 2025)
Objective: The current study aimed to develop and characterize a nanocrystal-based solid dispersion of Candesartan Cilexetil (CC) to improve its solubility and bioavailability. Methods: CC-loaded nanosuspension was prepared using the solvent precipitation method, employing Eudragit RLPO, and polyvinyl alcohol as a stabilizer. The resulting nano-sized lyophilized powder was then incorporated into a solid dispersion using the kneading method with crospovidone as a super-disintegrant. A 32 factorial design was used for optimization, with the amount of nanosuspension powder (X1) and concentration of superdisintegrant agent (X2) as independent variables. Evaluations included drug content (%), drug release (DR %), zeta potential (ZP), and other characterization techniques. Results: The optimized formulation, CCSD9, exhibited a particle size of 264 nm, a ZP of 20.32 mV, a DR rate of 99.45%, and a polydispersity index (PDI) of 0.365. Transmission electron microscopy analysis revealed drug nanocrystal agglomeration, possibly due to the water removal process. Differential scanning calorimetry analysis indicated a minor change in crystallinity, likely due to lactose presence, and confirmed no significant drug-excipient interaction. A 6-month stability trial was conducted. Conclusion: The solvent precipitation method proved to be an efficient approach for developing CC nanocrystal-based solid dispersion with a lower particle size. The nanosizing technique successfully encapsulated CC within the polymer matrix, enhancing DR and stability.